2015
DOI: 10.1016/j.sandf.2014.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-scale modeling of colloidal silica delivery to liquefiable sands

Abstract: Passive site stabilization is a developing technology for the in situ mitigation of the risk of liquefaction without surface disruption. It involves the injection of stabilizing materials into liquefiable saturated sand. In this study, a pilot-scale facility (243 cm by 366 cm in plan  122 cm deep) was used to inject a dilute colloidal silica stabilizer into liquefiable sand specimens. The grout advancement was monitored in real time using electrical conductivity cells embedded in the specimens. Injection rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…They believe that the maximum transport distance for CS ranges from 2.5 m to 4 m due to the higher density of CS solutions compared with pore water [67,68]. To further investigate the sinking behavior and horizontal movement of CS grouting, they developed a 10 m 3 pilot-scale box model [69], as shown in Figure 13. The loose sand layer was placed in the box model by freely pouring sand onto water.…”
Section: Injection Ratementioning
confidence: 99%
See 2 more Smart Citations
“…They believe that the maximum transport distance for CS ranges from 2.5 m to 4 m due to the higher density of CS solutions compared with pore water [67,68]. To further investigate the sinking behavior and horizontal movement of CS grouting, they developed a 10 m 3 pilot-scale box model [69], as shown in Figure 13. The loose sand layer was placed in the box model by freely pouring sand onto water.…”
Section: Injection Ratementioning
confidence: 99%
“…A low viscosity status should be sustained to facilitate CS horizontal transport. However, once CS arrives at the targeted location, sinking and deposition will occur on the condition of low viscosity [66][67][68][69][70]. Therefore, gel time is difficult to control in the conventional CS grouting method.…”
Section: Advancement For Cs Transportmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that the colloidal silica grout reduces considerably the rates of pore pressure generation and shear strain of the silty sand specimens subjected to cyclic loading. Recent studies have been conducted by Hamderi and Gallagher (2015) where bypassive site stabilization was develop for in situ mitigation of the risk of liquefaction without surface disruption. It involves the injection of stabilizing materials into liqueable saturated sand, injecting a dilute colloidal silica stabilizer into liquefiable sand specimens.…”
Section: Innovative Solutions To Mitigate Earthquake Induced Soil Liquefaction Damages (Eild)mentioning
confidence: 99%
“…The mechanism for colloidal silica transport in sand was studied [7][8]. Besides, different tests, such as full-scale explosion test [9], centrifuge tests [10][11][12] and tri-axial tests [13][14][15][16][17] were carried out to evaluate liquefaction mitigation of loose sand treated by colloidal silica.…”
Section: Introductionmentioning
confidence: 99%